Acremonium Chrysosprium and Related Keratinolytic Fungi in Soil of Himanchal Pradesh - Singh, Itisha (International Journal of Pharmaceutical & Biological Archive, 2014)
Acremonium Chrysosprium and Related Keratinolytic Fungi in Soil of Himanchal Pradesh